Dots of connected numbers as learning instrument computational thinking concept in elementary school - Wahyu Ridhoni; Darshil Makwana; Choirudin Choirudin (CV. Edutechnium Indonesia, 2023)
The skill needed by future generations when computers become more massive and more connected is to think like a computer. Computational thinking is a method of thinking commonly used by programmers when writing program code. There are four principles in computational thinking, (1) Decomposition, (2) Pattern Recognition, (3) Abstraction, and (4) Algorithm Design. The research was conducted in three stages: planning, development, and testing. The results obtained are that the dots of corresponding numbers can be a simple instrument to teach computational thinking but requires that children have mastered the sum operation. The four principles of computational thinking have been contained in the Dots of numbers connected.